Study on Fatigue Characteristics of Concrete Sleepers with Porous Basalt as the Aggregate - Shougang Huang (Faculty of Mechanical Engineering in Slavonski Brod, Faculty of Electrical Engineering in Osijek, Faculty of Civil Engineering in Osijek, 2021)
Due to the shortage of local materials, porous basalt was used as the coarse aggregate in the prefabrication of sleepers for the Mombasa-Nairobi Railway in Kenya. To study their fatigue characteristics, the sleepers were measured under fatigue loading for their local strain, overall deformation and crack initiation. The methods used include the traditional strain measurement, the sleeper deflection measurement and the 3D optical strain measurement. To be more specific, the traditional strain measurement method was employed to compare the strain-load relation of the sleepers under different cyclic loading times. Deflection variations of the sleepers were taken into consideration to analyze sleeper local defects and the variation law of the constitutive relation for concrete. And the 3D optical non-contact strain measurement method was adopted to monitor the sleeper crack initiation and growth process under fatigue loading and analyze the crack growth law.